Philosophical Discussion of Legal and Moral Relationships in Perspective of Natural Law and Legal Positivism - Achmad Soeharto; Taufik .; Ong Argo Victoria (Faculty of Law, Universitas Pekalongan, 2022)
The relationship between law and morals has become an academic and philosophical debate throughout the ages, especially in the schools of natural law and legal positivism. The school of natural law always relates law and morals in a close, inseparable relationship, like a coin. The law must contain moral values. Meanwhile, legal positivism clearly separates the relationship between law and morals. Thus the law is not at all related to morality, the problem of law contains moral values or not, not the substance and legal issues, the most important thing is that the law is made by a sovereign ruler. Law is separated from non-juridical elements, such as ethics, morals, politics, economics, sociology, and so on. In other words, the law is purified from something that is not law. With the very sharp differences between the two schools of law, the schools of natural law and legal positivism for hundreds of years have never agreed on the relationship between law and morals. Each has a paradigm, method, theory, and a strong philosophical basis in seeing the relationship between law and morals.Keywords: Natural Law, Legal Positivism, Law and Morals